1996
DOI: 10.1053/jhep.1996.v23.pm0008666330
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of hereditary hepatitis and liver tumor development in Long-Evans cinnamon rats by the copper-chelating agent trientine dihydrochloride

Abstract: long-term administration of the agent. The copper level Trientine dihydrochloride (trientine) is an alternative in the liver of treated rats was reduced by 33% at 87 medicinal copper chelating agent for patients with Wilweeks of age. Development of HCC in LEC rats might be son's disease of penicillamine intolerance. We examined partly, but not totally, because of copper accumulation. the effects of trientine on the spontaneous development No effects on the levels of copper, iron, or zinc in the of hepatitis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…Excessive accumulated copper is considered to be responsible for the hepatocarcinogenesis observed in LEC rats. 34 It is now well known that excess heavy metals, such as copper and iron, generate ROS such as superoxide anion and hydrogen peroxide, catalyzing the formation of highly toxic hydroxyl radicals via a Fenton-like reaction. 35 Hydroxyl radicals can then initiate lipid peroxidation chain reactions, thereby disrupting cellular membranes, mainly mitochondrial membranes, 36,37 and damage the DNA of both the mitochondria and nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive accumulated copper is considered to be responsible for the hepatocarcinogenesis observed in LEC rats. 34 It is now well known that excess heavy metals, such as copper and iron, generate ROS such as superoxide anion and hydrogen peroxide, catalyzing the formation of highly toxic hydroxyl radicals via a Fenton-like reaction. 35 Hydroxyl radicals can then initiate lipid peroxidation chain reactions, thereby disrupting cellular membranes, mainly mitochondrial membranes, 36,37 and damage the DNA of both the mitochondria and nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, copper chelating agents (D-penicillamine and trientine dihydrochloride) inhibited the development of liver tumors as well as hepatitis of LEC rats. [20][21][22] Iron-deficient diet also inhibits the development of liver tumors. 23) These data suggest that tumor development in LEC rats is a later event caused by chronic copper and/or iron toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…8) The reason for this is unknown, but the decrease of hepatic copper concentration by chelating agents may increase intestinal iron absorption or iron uptake into hepatocytes. 35) Lesions such as altered tubules 36) and atypical tubules and hyperplasia 37) are known as renal preneoplastic lesions in rodents.…”
Section: Discussionmentioning
confidence: 99%
“…7,8) Patients with Wilson's disease are known to have abnormal renal function and penicillamine therapy improves their renal function, 9) but we know of no reports of renal neoplasms in cases of Wilson's disease. We have reported that renal cell tumors develop spontaneously in LEC rats.…”
Section: Abstract: Renal Carcinogenesis -Spontaneous -Copper -Lec Ratmentioning
confidence: 99%
See 1 more Smart Citation